The Rules of Matn Criticism: There Are No Rules - Brown, Jonathan A. C. (Islamic law and society, 2012)
Abstract In an effort to avoid the subjectivity of individual reason, Sunni Islam elaborated a method of hadīth criticism that subordinated evaluating the meaning of a report to an examination of its chain of transmission. With the fourth/tenth-century epistemological compromise of Ash'arism, however, Sunni hadīth scholars adopted rationalist criteria of content criticism that included explicit rules for rejecting hadīths because of their meaning. This resulted in a strong internal tension within Sunni hadīth criticism from the fifth/eleventh century onwards, with one and the same scholar upholding rigid rules of content criticism but not employing them or even rejecting them in application. The inherent subjectivity of content criticism resulted in different Muslim scholars either rejecting or affirming the same hadīths. Some scholars were much more inclined to reject a hadīth out of hand because of its meaning, while others were willing to extend a hadīth more interpretive charity. The tension created by the subjectivity of content criticism emerged in unprecedented relief in the modern period, when 'science' and modern social norms presented an unmatched challenge to the interpretive awe in which pre-modern (and Traditionalist scholars today) held attributions to the Prophet.